Analisis Pengaruh Kesadaran Wajib Pajak Sanksi dan Tingkat Pemahaman Perpajakan terhadap Kepatuhan Wajib Pajak - Hasrul Siregar; Sri Juliana Sari Djakaria; Sovia Lolita Apriani Pardede; Mipo Mipo; Rifdah Dara Riyan; Corinna Wongsosudono (Universitas Islam Islam Sumatera Utara, 2023)
Taxes are one of the main sources of revenue for the state. In this case, tax revenues are used to fund government spending, including funding in the public interest. Therefore, awareness and compliance of taxpayers is very necessary. This study is a quantitative descriptive study conducted by the Medan Petisah Tax Service Office. The aim of this study is to determine the impact of taxpayer awareness, penalties and understanding of taxation on tax compliance. The population in this study were registered taxpayers at KPP Pratama Medan Petisah, totaling 133,938 people, and 100 respondents were interviewed. The variables in this study are taxpayer awareness (X1), sanctions (X2), taxpayer understanding level (X3), and taxpayer compliance (Y). The method used to collect respondent results using a questionnaire. Results showed that taxpayer awareness and understanding had a significant impact on tax compliance. While the tax penalty variable does not have a significant impact on tax compliance. The results of the t- test gave a p- value 0. 05 for the variables X1, X3, while for the control penalty variable (X2) the p- value was 0.05. The conclusion of this study is that taxpayer awareness, sanctions and taxpayer understanding have a significant impact on tax compliance at KPP Pratama Medan Petisah.